MEANING OF THE SOCIAL INSTITUTION OF HIGHER EDUCATION IN THE PROCESS OF BECOMING THE INFORMATION SOCIETY - Mikhail A. Ermakov (Высшее образование в России)
The empirical base of the article is the materials of the survey conducted in 2012 in Perm National Research Polytechnic University (PNRPU), which is one of the largest universities in Perm. The study was conducted by the method of a questionnaire survey. The objects of the research were the second-year and fourth-year students of PNRPU and also master degree students. The size of a sample is 799 people. We investigated the personality awareness of information society, in particular the opinion of respondents about higher education and its role in the transformation of society. The position of students, which implies underdevelopment of the information society, is illustrated. The key differences between information society model and the modern stage are selected.